Controllable Cross‐Linking Anion Exchange Membranes with Excellent Mechanical and Thermal Properties. Issue 3 (19th January 2018) - Wang, Chao; He, Zhenfeng; Xie, Xiaofeng; Mai, Xianmin; Li, Yingchun; Li, Tingxi; Zhao, Min; Yan, Chao; Liu, Hu; Wujcik, Evan K.; Guo, Zhanhu
Abstract: A new monomer called 2, 2′‐(4, 4′‐oxydiphenol‐4, 4′‐diyl)bis(2‐methyl‐2, 3, 3a, 4, 7, 7a‐hexahydro‐1H‐4, 7‐methanoisoindol‐2‐ium) iodide (d3 ) is synthesized possessing both cross‐linker and functional groups. The membranes are formed by copolymerizing d3 with norbornene and (3aR, 4S, 7R, 7aS)‐2‐methyl‐2‐(3‐(trimethylammonio)propyl)‐2, 3, 3a, 4, 7, 7a‐hexahydro‐1H‐4, 7‐methanoisoindol‐2‐ium iodide (a3 ) at varying ratios. The water uptake is 41.35% at 60 °C, and ion exchange capacity is 2.35 mequiv g −1 for a mole ratio of a3, norbornene, and d3 (1:6:3). The conductivity is 12, 37, and 40 mS cm −1 when d3 is decreased. Meanwhile, the conductivity increases quickly with increasing the temperature. Furthermore, the mechanical properties and thermal properties are improved, attributed to the increased cross‐linker. The membrane has a tensile strength of 41.3 MPa and the elongation at break of 38.0 %, and the 5 wt% loss temperature for membrane is ≈159 °C. The H2 /O2 single fuel cells with this membrane show a maximum power density of 124 mW cm −2 at 50 °C. The cross‐linked membranes demonstrate high‐dimensional stability in alkaline solution. Abstract : A kind of polymers for anion exchange membranes (AEMs) with different compositions is synthesized. These AEMs show good mechanical strength. Meanwhile, ion exchange capacity, conductivity, water uptake, swelling and thermal properties are all good enough for practical applications such as fuel cells arising from the high cross‐linkers of the modified system.